Kesalahan Siswa Dalam Memecahkan Masalah Perkalian dan Pembagian Pecahan di Kelas V Sekolah Dasar - Fidiya Desta Rafatalita Widiyantoro; Ryky Mandar Sary; Ikha Listyarini (Universitas Muhammadiyah Bangka Belitung, 2025)
The context of this research was driven by the observation of student errors in solving problems related to multiplication and division of fractions in fifth grade elementary school. This is due to the lack of understanding of fractions, which leads to errors when students work on these problems. This study aims to identify the types of errors and the factors causing students' misunderstandings in solving multiplication and division of fractions, based on Polya's problem-solving steps, in a fifth grade class at a public elementary school in Semarang Regency. The research approach is qualitative with a phenomenological research method. The data sources for this study are teachers and 23 students from class VB of a public elementary school in Semarang Regency. Data in this study were obtained through observations, written tests, interviews, and documentation. The data analysis technique involved data reduction, data presentation, and drawing conclusions. Data validity was ensured through technique and source triangulation. The results of the study indicate: (1) errors in understanding the problem amounted to 23.6%, in planning amounted to 22.2%, in executing the plan amounted to 51.3%, and in writing the final answer amounted to 69.4%. (2) The factors causing these problem-solving errors include students not being accustomed to noting known and asked information in the problems, students not having the habit of writing down a solution plan, students not knowing which steps to choose to create a plan, students not solving problems according to the pre-made plan, and students not thoroughly checking the steps.